2017
DOI: 10.1213/ane.0000000000002004
|View full text |Cite
|
Sign up to set email alerts
|

Generative Retrieval Improves Learning and Retention of Cardiac Anatomy Using Transesophageal Echocardiography

Abstract: Medical students and anesthesiology residents inexperienced in the use of TEE showed both improved learning and retention of basic cardiovascular ultrasound anatomy with the incorporation of GR into the educational experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Spaced learning was also implemented in simulation settings (n = 24, 23%), generally used to disperse training sessions over time to stimulate clinical skill acquisition. In total 24 studies (23%) were conducted in classrooms and applied to various educational activities, ranging from repeated practice and testing of basic science mechanisms, to clinical scenarios and skill training.…”
Section: Resultsmentioning
confidence: 99%
“…Spaced learning was also implemented in simulation settings (n = 24, 23%), generally used to disperse training sessions over time to stimulate clinical skill acquisition. In total 24 studies (23%) were conducted in classrooms and applied to various educational activities, ranging from repeated practice and testing of basic science mechanisms, to clinical scenarios and skill training.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, our research group found that generative retrieval was associated with increased retention of normal cardiovascular transesophageal echocardiography (TEE) anatomy in fourth-year medical students and postgraduate year 1 and 2 (PGY-1 and -2) anesthesiology residents (25). Perhaps more importantly, generative retrieval was a time efficient tool to learn TEE anatomy.…”
Section: Introductionmentioning
confidence: 95%
“…Recent advances in memory research suggest that learning involving repeated testing may enhance long-term retention of information and knowledge merely by the practice of retrieval from memory (19,23,25). When learners are encouraged to attempt to recover items from memory (even before being taught the material), they are more likely to retain information compared with those who were asked only to study the given information (28).…”
Section: Introductionmentioning
confidence: 99%
“…Esta relação entre conhecimentos prévios e conhecimentos novos, que estão sendo construídos, é um aspecto importante. Estudos recentes demonstram que, quando os estudantes ativamente mobilizam conhecimentos prévios relacionados ao conteúdo que está sendo trabalhado inicia-se o processo de reconsolidação da memória, o qual desencadeia uma série de processos neuroquímicos que estimulam a neuroplasticidade sináptica, permitindo o fortalecimento ou ampliação dos conhecimentos do aprendente (SOSA et al, 2018;KLEIMAN et al, 2017;KHOIRIYAH et al, 2015).…”
Section: Múltiplas Representações E Aspectos Da Memóriaunclassified